EDUCATION MOVEMENT OF SHIA GROUP IN CONTEMPORARY INDONESIA - Dahlia Lubis; Syarifah Rahmah (UIN Sumatera Utara, 2021)
Abstract: The aim of this research is to look at the Shia educational movement in Indonesia as it develops its philosophy. Document study activities, observation, and interviews were used to gather data. Two findings were offered in this study. The first is marriage, which is a technique for expanding the number of Shiites in Indonesia by allowing a husband and wife to establish an Islamic family structure based on Shia beliefs. In this setting, the family serves as the primary educational institution in Indonesia for the young Shia generation. The second, internalization of information, attitudes, and abilities, takes place in activities created by Islamic organizations and foundations founded by Shia groups in Indonesia. The many organizations and foundations involved in education and religion have formed a venue for Shia community education in introducing and propagating their schools of thought.Keywords: educational institutions, shia, minority groups